Accounting outsourcing in micro and small entities − opportunities and threats - Maszczak, Teresa (Outsourcing rachunkowości w mikro- i małych podmiotach – szanse i zagrożenia, 2019)
In the era of social and economic transformations, strong competition, as well as changing legal regulations, it is possible to stay on the market and for micro and small entities to operate effectively by outsourcing the provision of accounting services to highly specialised entities. Aim of the article: to present the role of accounting outsourcing in terms of information needs of users of small and micro entities operating on the global market, as well as to point out their opportunities and threats in the light of the results of the conducted research. Research methods: studies of the subject literature, review of legal acts, survey method, inference. Research results: benefits (opportunities): focus on the implementation of key tasks, identification and reduction of the risk of threat to financial liquidity, reduction of labour costs, better effectiveness without investing; threats: confidentiality of company information, changes in legal regulations, increase in service prices
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 8, s. 92-107
Keywords: outsourcing; accounting; economical information; rachunkowość; informacje ekonomiczne